Psychosocial skills in a youth soccer academy: A holistic ecological perspective - Hvid Larsen, C.; Alfermann, D.; Krogh Christensen, M. (Sport Science Review, 2012)
The latest research in talent development show that more varied psychological and especially social and cultural circumstances play an important role in talent development. This study assumes an ecological approach to explore which psychosocial skills are important in a youth soccer academy and how psychosocial skills are practiced in this particular environment. Method: The research takes the form of a case study. Data were collected from multiple perspectives (in-depth interviews with managers, coaches and players), from multiple situations (observation of training, competitions and meetings) and from the analysis of documents. Results: The findings reveal explicit (being practiced and talked about) and implicit (indirectly practiced and talked about) psychosocial skills in the youth soccer academy and a differentiation between internal and interpersonal psychosocial skills. Conclusions: Important explicit psychosocial skills are motivation, self awareness and the ability to work hard. However, even more important for the young soccer players dealing with the transition to professional soccer seem to be implicit psychosocial skills such as managing performance and process outcomes (internal) and the ability to utilize team skills and general social skills (interpersonal). Despite the fact that the environment expects the young players to display these skills, they are only indirectly practiced. This study demonstrates the interweaving of psychosocial skills and practice in the talent development environment, and thus underlines the social construction of psychosocial skills in elite sport.